Reduced evapotranspiration from leaf beetle induced tamarisk defoliation in the Lower Virgin River using satellite‐based energy balance. Issue 1 (7th April 2015) - Liebert, Ryan; Huntington, Justin; Morton, Charles; Sueki, Sachiko; Acharya, Kumud
Abstract: Tamarisk ( Tamarix spp.) is an invasive shrubby tree native to Eurasia. Since its introduction to the United States, it has established itself along Southwestern American riparian systems. Control programs aimed at removing tamarisk were initiated in an effort to restore riparian areas, and potentially salvage water. Biological control of tamarisk with the Diorhabda spp. (leaf beetles) defoliates tamarisk and reduces evapotranspiration (ET). In 2009, the beetle arrived at Mesquite, Nevada, along the Virgin River, and dispersed to the Lower Virgin River riparian area in 2011. This study estimates reduced Lower Virgin River riparian ET caused by leaf beetle activity. Multi‐temporal spectral angle mapper was used to detect established leaf beetle communities in the Lower Virgin River riparian area. The Mapping Evapotranspiration at High Resolution with Internal Calibration (METRIC) land surface energy balance model was used to estimate Lower Virgin River riparian ET. METRIC ET results were compared with eddy covariance ET estimates made in tamarisk along the Lower Virgin River. Comparisons indicated that METRIC accurately estimates pre‐beetle ET and post‐beetle reduced ET. The 2007–2010 (pre‐beetle) average ET for the Lower Virgin River riparian area was 1245 mm/yr compared with 1041 mm/yr for the 2011–2012 (post‐beetle) period. Given the 4700 acre riparian area, leaf beetle induced defoliation results in a mean annual ET reduction of 3161 acre‐ft. In 2011 and 2012, volumetric reductions to ET were estimated to be 817 and 5505 acre‐ft, respectively. The METRIC model was shown to be a useful tool for monitoring ET during pre‐beetle and post‐beetle defoliation periods. Copyright © 2015 John Wiley & Sons, Ltd.